Further description of two patients with biallelic variants in NADSYN1 in association with cardiac and vertebral anomalies. Issue 8 (2nd May 2022) - Kortbawi, Hannah; Ames, Elizabeth; Pritchard, Amanda; Devine, Patrick; van Ziffle, Jessica; Slavotinek, Anne
Abstract: Congenital nicotinamide adenine dinucleotide (NAD) deficiency disorders are associated with pathogenic variants in the genes NADSYN1, HAAO, and KYNU . These disorders overlap with the anomalies present in vertebral, anal, cardiac, tracheoesophageal, radial and renal, and limb anomalies (VATER/VACTERL) association and often result in premature death. Children who survive typically have developmental delays or intellectual disability. Here, we describe two patients with compound heterozygous variants in NADSYN1 who presented with cardiac and vertebral defects overlapping with the VATER/VACTERL association, although the patients did not satisfy criteria for the diagnosis of VATER/VACTERL due to their lack of limb anomalies and significant renal anomalies. One patient survived into childhood with developmental delays and may represent an expansion of the survival data for NADSYN1‐ associated NAD deficiency disorders. Interestingly, one patient had hypoplastic left heart syndrome (HLHS) and one had an aortic coarctation and transverse hypoplasia of the aortic arch, suggesting that NADSYN1 sequencing should be performed in children presenting with congenital anomalies related to VATER/VACTERL association and with HLHS and aortic arch abnormalities.